Analysis of RIM Expression and Function at Mouse Photoreceptor Ribbon Synapses - Löhner, Martina; Babai, Norbert; Müller, Tanja; Gierke, Kaspar; Atorf, Jenny; Joachimsthaler, Anneka; Peukert, Angela; Martens, Henrik; Feigenspan, Andreas; Kremers, Jan; Schoch, Susanne; Brandstätter, Johann Helmut; et al. (The Journal of Neuroscience, 2017)
RAB3A-interacting molecule (RIM) proteins are important regulators of transmitter release from active zones. At conventional chemical synapses, RIMs contribute substantially to vesicle priming and docking and their loss reduces the readily releasable pool of synaptic vesicles by up to 75%. The priming function of RIMs is mediated via the formation of a tripartite complex with Munc13 and RAB3A, which brings synaptic vesicles in close proximity to Ca(2+) channels and the fusion site and activates Munc13. We reported previously that, at mouse photoreceptor ribbon synapses, vesicle priming is Munc13 independent. In this study, we examined RIM expression, distribution, and function at male and female mouse photoreceptor ribbon synapses. We provide evidence that RIM1? and RIM1? are highly likely absent from mouse photoreceptors and that RIM2? is the major large RIM isoform present at photoreceptor ribbon synapses. We show that mouse photoreceptors predominantly express RIM2 variants that lack the interaction domain for Munc13. Loss of full-length RIM2? in a RIM2? mutant mouse only marginally perturbs photoreceptor synaptic transmission. Our findings therefore strongly argue for a priming mechanism at the photoreceptor ribbon synapse that is independent of the formation of a RIM-Munc13-RAB3A complex and thus provide further evidence for a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses in synaptic vesicle exocytosis.SIGNIFICANCE STATEMENT RAB3A-interacting molecules 1 and 2 (RIM1/2) are essential regulators of exocytosis. At conventional chemical synapses, their function involves Ca(2+) channel clustering and synaptic vesicle priming and docking through interactions with Munc13 and RAB3A, respectively. Examining wild-type and RIM2 mutant mice, we show here that the sensory photoreceptor ribbon synapses most likely lack RIM1 and predominantly express RIM2 variants that lack the interaction domain for Munc13. Our findings demonstrate that the photoreceptor-specific RIM variants are not essential for synaptic vesicle priming at photoreceptor ribbon synapses, which represents a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses with respect to synaptic vesicle priming mechanisms.
EVALuna2:21339

Ccdc66 null mutation causes retinal degeneration and dysfunction - Gerding, Wanda M.; Schreiber, Sabrina; Schulte-Middelmann, Tobias; Marques, Andreia De Castro; Atorf, Jenny; Akkad, Denis A.; Dekomien, Gabriele; Kremers, Jan; Dermietzel, Rolf; Gal, Andreas; Ruelicke, Thomas; Ibrahim, Saleh; et al. (Human Molecular Genetics, 2011)
Retinitis pigmentosa (RP) is a group of human retinal disorders, with more than 100 genes involved in retinal degeneration. Canine and murine models are useful for investigating human RP based on known, naturally occurring mutations. In Schapendoes dogs, for example, a mutation in the CCDC66 gene has been shown to cause autosomal recessively inherited, generalized progressive retinal atrophy (gPRA), the canine counterpart to RP. Here, a novel mouse model with a disrupted Ccdc66 gene was investigated to reveal the function of protein CCDC66 and the pathogenesis of this form of gPRA. Homozygous Ccdc66 mutant mice lack retinal Ccdc66 RNA and protein expression. Light and electron microscopy reveal an initial degeneration of photoreceptors already at 13 days of age, followed by a slow, progressive retinal degeneration over months. Retinal dysfunction causes reduced scotopic a-wave amplitudes, declining from 1 to 7 months of age as well as an early reduction of the photopic b-wave at 1 month, improving slightly at 7 months, as evidenced by electroretinography. In the retina of the wild-type (WT) mouse, protein CCDC66 is present at highest levels after birth, followed by a decline until adulthood, suggesting a crucial role in early development. Protein CCDC66 is expressed predominantly in the developing rod outer segments as confirmed by subcellular analyses. These findings illustrate that the lack of protein CCDC66 causes early, slow progressive rod-cone dysplasia in the novel Ccdc66 mutant mouse model, thus providing a sound foundation for the development of therapeutic strategies.
EVALuna2:21029

Cell types and synapses expressing the snare complex regulating proteins complexin 1 and complexin 2 in mammalian retina - Lux, Uwe; Ehrenberg, Johanna; Joachimsthaler, Anneka; Atorf, Jenny; Pircher, Bianca; Reim, Kerstin; Kremers, Jan; Gießl, Andreas; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2021)
Complexins (Cplxs) 1 to 4 are components of the presynaptic compartment of chemical synapses where they regulate important steps in synaptic vesicle exocytosis. In the retina, all four Cplxs are present, and while we know a lot about Cplxs 3 and 4, little is known about Cplxs 1 and 2. Here, we performed in situ hybridization experiments and bioinformatics and exploited Cplx 1 and Cplx 2 single-knockout mice combined with immunocytochemistry and light microscopy to characterize in detail the cell type and synapse-specific distribution of Cplx 1 and Cplx 2. We found that Cplx 2 and not Cplx 1 is the main isoform expressed in normal and displaced amacrine cells and ganglion cells in mouse retinae and that amacrine cells seem to operate with a single Cplx isoform at their conventional chemical synapses. Surprising was the finding that retinal function, determined with electroretinographic recordings, was altered in Cplx 1 but not Cplx 2 single-knockout mice. In summary, the results provide an important basis for future studies on the function of Cplxs 1 and 2 in the processing of visual signals in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Amacrine cells; Complexin 1; Complexin 2; Conventional chemical synapses; Ganglion cells; Horizontal cells; Retina

Electroretinographic Recordings in a Mouse Model for CSNB2 Featuring Mutations in the Cacna1f Gene - Atorf, Jenny; Specht, D.; Maw, M.; Brandstätter, Johann Helmut; Dieck, S. Tom; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; electroretinography: non-clinical; synapse

Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration

Heterogeneous presynaptic distribution of munc13 isoforms at retinal synapses and identification of an unconventional bipolar cell type with dual expression of munc13 isoforms: A study using munc13-exfp knock-in mice - Gierke, Kaspar; von Wittgenstein, Julia; Hemmerlein, Maike; Atorf, Jenny; Joachimsthaler, Anneka; Kremers, Jan; Cooper, Benjamin H.; Varoqueaux, Frederique; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2020)
Munc13 isoforms are constituents of the presynaptic compartment of chemical synapses, where they govern important steps in preparing synaptic vesicles for exocytosis. The role of Munc13-1,-2 and-3 is well documented in brain neurons, but less is known about their function and distribution among the neurons of the retina and their conventional and ribbon-type chemical synapses. Here, we examined the retinae of Munc13-1-,-2-, and-3-EXFP knock-in (KI) mice with a combination of immunocytochemistry, physiology, and electron microscopy. We show that knock-in of Munc13-EXFP fusion proteins did not affect overall retinal anatomy or synapse structure, but slightly affected synaptic transmission. By labeling Munc13-EXFP KI retinae with specific antibodies against Munc13-1,-2 and-3, we found that unlike in the brain, most retinal synapses seem to operate with a single Munc13 isoform. A surprising exception to this rule was type 6 ON bipolar cells, which expressed two Munc13 isoforms in their synaptic terminals, ubMunc13-2 and Munc13-3. The results of this study provide an important basis for future studies on the contribution of Munc13 isoforms in visual signal processing in the mammalian retina.
CRIS-Team Scopus Importer:2020-11-06
Keywords: BrMunc13-2; Conventional synapse; Munc13-1; Munc13-3; Retina; Ribbon synapse; Type 6 ON bipolar cell; UbMunc13-2

Identification and immunocytochemical characterization of Piccolino, a novel Piccolo splice variant selectively expressed at sensory ribbon synapses of the eye and ear - Regus-Leidig, Hanna; Ott, Corinna; Löhner, Martina; Atorf, Jenny; Fuchs, Michaela; Sedmak, Tina; Kremers, Jan; Fejtova, Anna; Gundelfinger, Eckart D.; Brandstätter, Johann Helmut (PLoS ONE, 2013)
Piccolo is one of the largest cytomatrix proteins present at active zones of chemical synapses, where it is suggested to play a role in recruiting and integrating molecules relevant for both synaptic vesicle exo- and endocytosis. Here we examined the retina of a Piccolo-mutant mouse with a targeted deletion of exon 14 in the Pclo gene. Piccolo deficiency resulted in its profound loss at conventional chemical amacrine cell synapses but retinal ribbon synapses were structurally and functionally unaffected. This led to the identification of a shorter, ribbon-specific Piccolo variant, Piccolino, present in retinal photoreceptor cells, bipolar cells, as well as in inner hair cells of the inner ear. By RT-PCR analysis and the generation of a Piccolino-specific antibody we show that non-splicing of intron 5/6 leads to premature translation termination and generation of the C-terminally truncated protein specifically expressed at active zones of ribbon synapse containing cell types. With in situ proximity ligation assays we provide evidence that this truncation leads to the absence of interaction sites for Bassoon, Munc13, and presumably also ELKS/CAST, RIM2, and the L-type Ca(2) (+) channel which exist in the full-length Piccolo at active zones of conventional chemical synapses. The putative lack of interactions with proteins of the active zone suggests a function of Piccolino at ribbon synapses of sensory neurons different from Piccolo's function at conventional chemical synapses.
EVALuna2:21139

Multifocal Electroretinography with simultaneous fundus imaging in mice - Dutescu, R. Michael; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 508 electrophysiology: non-clinical; 578 laser; 612 neuro-ophthalmology: diagnosis

Multifocal ERG recordings under visual control of the stimulated fundus in mice - Dutescu, Ralf M.; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia M.; Strauss, Olaf; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Therapeutic approaches to retinal disease require a continuous monitoring of functional improvement over lesion areas that sometimes cannot be shown in full-field ERG. The aim of this study was to assess the usefulness of multifocal electroretinograms (mfERGs) under visual control using scanning laser ophthalmoscopy (SLO) for evaluation of local retinopathy in mice.mfERGs were optimized for recordings in C57BL/6 mice by varying dark steps between each stimuli, background intensity, and the numbers of hexagons. Local retinopathy was induced by argon laser photocoagulation with different spot sizes and retinal irradiances. mfERG recordings were performed before, and 10 days and 4 weeks after laser treatment. In each recording, the central hexagon was positioned on the optic nerve head visualized by SLO images. The amplitudes of the P1 response components were analyzed as a function of retinal location.The mfERG amplitudes depended on stimulus condition. The P1 amplitudes increased with increasing number of dark frames in the m-sequence and with decreasing number of hexagons. A stimulus with 19 hexagons and four dark frames was chosen because substantial response amplitudes could be achieved while preserving sufficient spatial resolution. In the untreated eyes, the response to the central hexagon, stimulating the optic nerve head, was smaller than those to the surrounding hexagons. The responses to hexagons stimulating photocoagulated areas were reduced compared with the responses of surrounding areas. The amplitude reduction was more pronounced when the coagulated areas were larger and when higher energies were used.Areas with decreased sensitivities to light stimulation (either the optic nerve head or damaged retinal areas) can be detected and correlated with the retinal images and in the mfERG responses. We demonstrate that the mfERG technique is able to reproducibly detect the functional consequences of a local treatment.
EVALuna2:21138

Mutation in Bmpr1b Leads to Optic Disc Coloboma and Ventral Retinal Gliosis in Mice - Yan, Xiaohe; Atorf, Jenny; Ramos, David; Thiele, Frank; Weber, Susanne; Dalke, Claudia; Sun, Minxuan; Puk, Oliver; Michel, Dian; Fuchs, Helmut; Klaften, Matthias; Przemeck, Gerhard K. H.; et al. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. The clinical phenotype of retinal gliosis occurs in different forms; here, we characterize one novel genetic feature, (i.e., signaling via BMP-receptor 1b).
CRIS-Team WoS Importer:2020-03-20

Photoreceptor degeneration in two mouse models for congenital stationary night blindness type 2 - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Kremers, Jan; Maw, Marion A.; Brandstätter, Johann Helmut (PLoS ONE, 2014)
Light-dependent conductance changes of voltage-gated Cav1.4 channels regulate neurotransmitter release at photoreceptor ribbon synapses. Mutations in the human CACNA1F gene encoding the ?1F subunit of Cav1.4 channels cause an incomplete form of X-linked congenital stationary night blindness (CSNB2). Many CACNA1F mutations are loss-of-function mutations resulting in non-functional Cav1.4 channels, but some mutations alter the channels' gating properties and, presumably, disturb Ca(2+) influx at photoreceptor ribbon synapses. Notably, a CACNA1F mutation (I745T) was identified in a family with an uncommonly severe CSNB2-like phenotype, and, when expressed in a heterologous system, the mutation was shown to shift the voltage-dependence of channel activation, representing a gain-of-function. To gain insight into the pathomechanism that could explain the severity of this disorder, we generated a mouse model with the corresponding mutation in the murine Cacna1f gene (I756T) and compared it with a mouse model carrying a loss-of-function mutation (?Ex14-17) in a longitudinal study up to eight months of age. In ?Ex14-17 mutants, the b-wave in the electroretinogram was absent, photoreceptor ribbon synapses were abnormal, and Ca(2+) responses to depolarization of photoreceptor terminals were undetectable. In contrast, I756T mutants had a reduced scotopic b-wave, some intact rod ribbon synapses, and a strong, though abnormal, Ca(2+) response to depolarization. Both mutants showed a progressive photoreceptor loss, but degeneration was more severe and significantly enhanced in the I756T mutants compared to the ?Ex14-17 mutants.
EVALuna2:21185

Rod- and cone-driven responses in mice expressing human L-cone pigment - Tsai, Tina I.; Atorf, Jenny; Neitz, Maureen; Neitz, Jay; Kremers, Jan (Journal of Neurophysiology, 2015)
The mouse is commonly used for studying retinal processing, primarily because it is amenable to genetic manipulation. To accurately study photoreceptor driven signals in the healthy and diseased retina, it is of great importance to isolate the responses of single photoreceptor types. This is not easily achieved in mice because of the strong overlap of rod and M-cone absorption spectra (i.e., maxima at 498 and 508 nm, respectively). With a newly developed mouse model (Opn1lw(LIAIS)) expressing a variant of the human L-cone pigment (561 nm) instead of the mouse M-opsin, the absorption spectra are substantially separated, allowing retinal physiology to be studied using silent substitution stimuli. Unlike conventional chromatic isolation methods, this spectral compensation approach can isolate single photoreceptor subtypes without changing the retinal adaptation. We measured flicker electroretinograms in these mutants under ketamine-xylazine sedation with double silent substitution (silent S-cone and either rod or M/L-cones) and obtained robust responses for both rods and (L-)cones. Small signals were yielded in wild-type mice, whereas heterozygotes exhibited responses that were generally intermediate to both. Fundamental response amplitudes and phase behaviors (as a function of temporal frequency) in all genotypes were largely similar. Surprisingly, isolated (L-)cone and rod response properties in the mutant strain were alike. Thus the LIAIS mouse warrants a more comprehensive in vivo assessment of photoreceptor subtype-specific physiology, because it overcomes the hindrance of overlapping spectral sensitivities present in the normal mouse.
EVALuna2:21228

Rod photoreceptor ribbon synapses in DBA/2J mice show progressive age-related structural changes. - Fuchs, Michaela; Scholz, Michael; Sendelbeck, Anna; Atorf, Jenny; Schlegel, Christine Julie; Enz, Ralf; Brandstätter, Johann Helmut (PLoS ONE, 2012)
The DBA/2J mouse is a commonly used animal model in glaucoma research. The eyes of DBA/2J mice show severe age-related changes that finally lead to the degeneration of retinal ganglion cells and the optic nerve. Recent electroretinogram studies identified functional deficits, which suggest that also photoreceptor cells are involved in the pathological processes occurring in the DBA/2J mouse retina. In a comparative study, we examined anatomical and molecular changes in the retinae of DBA/2J and C57BL/6 control mice with light and electron microscopy and with PCR analyses. In the retina of the DBA/2J mouse, we found a thinning of the outer plexiform layer, the first synaptic layer in the transfer of visual signals, and age-dependent and progressive degenerative structural changes at rod photoreceptor ribbon synapses. The structural ribbon changes represent a photoreceptor synaptic phenotype that has not yet been described in this animal model of secondary angle-closure glaucoma. Furthermore, genes of the classical complement cascade were upregulated in the photoreceptor cells of aging DBA/2J mice, suggesting a putative link between ribbon synapse degradation and the innate immune system. © 2012 Fuchs et al.
UnivIS-Import:2015-04-14:Pub.2012.med.IB.profes_1.rodpho

Strain differences in illumination-dependent structural changes at mouse photoreceptor ribbon synapses - Fuchs, Michaela; Sendelbeck, Anna; Atorf, Jenny; Kremers, Jan; Brandstätter, Johann Helmut (Journal of Comparative Neurology, 2013)
Photoreceptor cells encode light signals over a wide range of intensities with graded changes in their membrane potential. At their highly specialized ribbon synapses they transmit the signals to the postsynaptic neurons by the tonic release of glutamate, which is continuously adjusted to changes in light intensity. Such a level of performance requires adaptive mechanisms, and it is suggested that illumination-dependent changes in ribbon shape and size are one of these adaptive processes. In this study we compared structural properties of synaptic ribbons under various illumination conditions between three mouse strains: the pigmented C57BL/6 and the two albino strains Balb/c and B6(Cg)-Tyr(c-2J) /J (coisogenic to C57BL/6). In addition, electroretinograms (ERGs) recorded in the same groups were compared. In the C57BL/6 mouse a change in illumination did not result in structural alterations of the synaptic ribbon. Similarly, in the B6(Cg)-Tyr(c-2J) /J mouse only minor structural changes were detected. In contrast, the state of adaptation had a large influence on the ribbon structure of the Balb/c mouse. The ERG recordings showed only small functional differences between C57BL/6 and B6(Cg)-Tyr(c-2J) /J mice, but the retinal function of Balb/c mice was strongly compromised. We conclude that illumination-dependent changes of photoreceptor ribbon structure differ between strains and thus cannot be regarded as a general mechanism for light adaptation.
EVALuna2:21087

The BEACH Protein LRBA Promotes the Localization of the Heterotrimeric G-protein Golf to Olfactory Cilia - Kurtenbach, Stefan; Gießl, Andreas; Stromberg, Siv; Kremers, Jan; Atorf, Jenny; Rasche, Sebastian; Neuhaus, Eva M.; Herve, Denis; Brandstätter, Johann Helmut; Asan, Esther; Hatt, Hanns; Kilimann, Manfred W. (Scientific Reports, 2017)
BEACH domain proteins are involved in membrane protein traffic and human diseases, but their molecular mechanisms are not understood. The BEACH protein LRBA has been implicated in immune response and cell proliferation, and human LRBA mutations cause severe immune deficiency. Here, we report a first functional and molecular phenotype outside the immune system of LRBA-knockout mice: compromised olfaction, manifesting in reduced electro-olfactogram response amplitude, impaired food-finding efficiency, and smaller olfactory bulbs. LRBA is prominently expressed in olfactory and vomeronasal chemosensory neurons of wild-type mice. Olfactory impairment in the LRBA-KO is explained by markedly reduced concentrations (20-40% of wild-type levels) of all three subunits ?olf, ?1 and ?13 of the olfactory heterotrimeric G-protein, Golf, in the sensory cilia of olfactory neurons. In contrast, cilia morphology and the concentrations of many other proteins of olfactory cilia are not or only slightly affected. LRBA is also highly expressed in photoreceptor cells, another cell type with a specialized sensory cilium and heterotrimeric G-protein-based signalling; however, visual function appeared unimpaired by the LRBA-KO. To our knowledge, this is the first observation that a BEACH protein is required for the efficient subcellular localization of a lipid-anchored protein, and of a ciliary protein.
EVALuna2:21341

The Photoreceptor Ribbon Synapse in the Absence of Piccolo: An RNAi Approach - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Boye, S.; Chiodo, V.; Seigel, G. M.; Hauswirth, W. W.; Kremers, Jan; Brandstätter, Johann Helmut (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; synapse